The Impact of Backspin Release Modes on Basketball Spin Axis Alignment - Madelyn Carniglia; Nathan Slegers (Journal of Coaching and Sports Science)
Background: Ball backspin is created during a basketball's final release. The complex nature of the hand-ball interaction at the moment of release can result in spin axis (SA) misalignment, which decreases shooting accuracy.